2017
DOI: 10.18433/j36c8n
|View full text |Cite
|
Sign up to set email alerts
|

Does Evolocumab, as a PCSK9 Inhibitor, Ameliorate the Lipid Profile in Familial Hypercholesterolemia Patients? A Meta-Analysis of Randomized Controlled Trials

Abstract: -Proprotein convertase subtilisin-kexin type 9 (PCSK9) is a member of regulatory serine proteases which is mostly expressed in liver. In the physiological condition, LDL-C binds to LDL receptors (LDLRs) and via endocytosis, LDLRs are degraded. PCSK9 binds to the epidermal growth factor-like repeat A (EGFA) domain of extracellular LDLRs, and then physiological recycling of LDLRs from surface of liver is cancelled, resulting in elevation of circulating LDL-C in plasma. To evaluate whether evolucomab, as PCSK9 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Among these studies, there were two in FH patients. However, one report studied the role and safety of evolocumab but did not include alirocumab [ 33 ]. In another study, although the role and safety of PCSK9-mAbs, including evolocumab and alirocumab, were discussed, the patients with FH were controversial because the data extracted by the authors did not exclude the non-FH patients included in the clinical study [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among these studies, there were two in FH patients. However, one report studied the role and safety of evolocumab but did not include alirocumab [ 33 ]. In another study, although the role and safety of PCSK9-mAbs, including evolocumab and alirocumab, were discussed, the patients with FH were controversial because the data extracted by the authors did not exclude the non-FH patients included in the clinical study [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Currently available data have demonstrated fewer untoward muscle-related adverse effects as well as greater LDL-C reductions in statin-intolerant patients administered with the fully monoclonal antibody to PCSK9 ( Moriarty et al, 2015 ; Nissen et al, 2016 ). Findings from a meta-analysis of randomized controlled trials have indicated that evolocumab could be a hopeful agent for challenging patients, such as those having statin intolerance or patients who fail to attain the target goal of LDL-C despite consumption of maximum doses of statins ( Eslami et al, 2017 ). Our results suggest that DXXK, a marketed product commonly used in atherosclerotic CAD, has good clinical value and may support statin action due to the reversal of PCSK9/LDLR expression in ApoE –/– mice revealed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…By combining with the epidermal growth factor-like repeat A domain (EGF-A) of low-density lipoprotein receptor (LDLR) and lowing the recycling of LDLR to cell surface, PCSK9 mediates serum LDL-C levels. Recently, several PCSK9 inhibitors, such as alirocumab and evolocumab, were applied in patients with familial hypercholesterolemia and/or CAD in different countries, and were verified to decrease total cholesterol (TC), LDL-C, triglyceride (TG) and the ratio of TC to high-density lipoprotein cholesterol (HDL-C) greatly [6].…”
Section: Introductionmentioning
confidence: 99%